PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN INDEX CARD MATCH PADA PELAJARAN FIKIH KELAS V DI MIS AL-ANWAR - Abidin, Zainal; Khairunnisa, Khairunnisa; Munte, Rahma Nadira Br; Valiza, Dinda; Mahfi, Icha Alfira; Nazlia, Rizki (HIBRUL ULAMA, 2024)
The aim of this research is to improve the fiqh learning outcomes of class V students through the Index Card Match learning model at MIS Al-Anwar. The research process was carried out in two cycles, namely cycle I and cycle II, using the planning, implementation, observation and reflection stages as the stages of classroom action research (PTK). At the same time, information is collected by quantitative means, such as tests and observations, which are then subjected to statistical analysis. After that, a descriptive qualitative approach was used to interpret the research findings. According to research findings, only two out of twelve students had completed their assignments with an average grade of 42.5, or 16%, before the action (pre-cycle). Students showed an increase in learning outcomes in cycle I, with an average score of 70.16, or 83%, and 10 out of 12 students passed. Meanwhile, students in cycle II showed significant improvement, with an average score of 74.16, or 91%, and 11 out of 12 students passed. The results of cycle I observations of teachers and students produced a score of 3.81 for teachers and 28.3 for students in the good category. In cycle II, students obtained a score of 48.3 which was classified as satisfactory, while the teacher's observation results obtained a score of 5.00. In summary, the findings of this research show that class V students at MIS Al-Anwar can improve their fiqh learning outcomes through the Index Card Match learning model.